2014
DOI: 10.1242/jcs.139253
|View full text |Cite
|
Sign up to set email alerts
|

A central region of Gli2 regulates its localization to the primary cilium and transcriptional activity

Abstract: Signaling through vertebrate Hedgehog (Hh) proteins depends on the primary cilium. In response to Hh signals, the transcriptional activator of the pathway, Gli2, accumulates at the ciliary tip, raising the possibility that ciliary localization is important for Gli2 activation. To test this hypothesis, we used the Floxin system to create knockin Gli2 alleles in embryonic stem cells (ESCs) to allow methodical testing of which domains and residues are essential for the ciliary localization of Gli2. The Gli2 zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 67 publications
(100 reference statements)
4
57
0
1
Order By: Relevance
“…Mice homozygous for the Gli2-EGFP allele are viable and morphologically indistinguishable from WT, revealing that this fusion protein is functional (8). To investigate the function of GLI2 in medulloblastoma, we incorporated the Gli2-EGFP allele into 2 established mouse models of Hh-associated medulloblastoma.…”
Section: Resultsmentioning
confidence: 99%
“…Mice homozygous for the Gli2-EGFP allele are viable and morphologically indistinguishable from WT, revealing that this fusion protein is functional (8). To investigate the function of GLI2 in medulloblastoma, we incorporated the Gli2-EGFP allele into 2 established mouse models of Hh-associated medulloblastoma.…”
Section: Resultsmentioning
confidence: 99%
“…It is crucial, however, to distinguish between the inability to respond to Hh pathway activation and the damage to the intrinsic transcriptional activity of the non-ciliary variant of Gli2. For example, a recent study found that the ciliary localization of a Gli2 variant lacking residues 852-1183 was greatly compromised compared with the full-length Gli2 (Santos and Reiter, 2014). However, this Gli2 variant acted as a transcriptional repressor when it was overexpressed, suggesting that the deletion has damaged its intrinsic transcriptional activator activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have reported physical interactions between Sufu truncation mutants (e.g., the N-terminal fragment of Sufu) and Gli proteins (Merchant et al 2004). Moreover, Gli2 (ΔSYGH) can still bind Sufu (Santos and Reiter 2014), suggesting the presence of multiple Sufu-binding domains in Gli2. It is possible that Sufu in a multiprotein complex in its native environment would display complex dynamic behaviors, and multiple domains of Sufu and Gli can interact with each other independently.…”
Section: The Multiple Roles Of Sufu In Controlling Gli Protein Functionsmentioning
confidence: 94%
“…It is possible that Sufu in a multiprotein complex in its native environment would display complex dynamic behaviors, and multiple domains of Sufu and Gli can interact with each other independently. In addition, Gli2 (ΔSYGH) is not sequestered in the cytoplasm and instead is enriched in the nucleus but does not lead to Hh pathway hyperactivation (Santos and Reiter 2014). This suggests that Sufu can inhibit Gli2 (ΔSYGH) activity in the nucleus, although it does not sequester Gli2 (ΔSYGH) in the cytoplasm.…”
Section: The Multiple Roles Of Sufu In Controlling Gli Protein Functionsmentioning
confidence: 99%